1976
DOI: 10.1016/s0006-3495(76)85686-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conditioning potential on potassium current kinetics in the frog node

Abstract: The kinetics of potassium conductance changes were determined in the voltage clamped frog node (Rana esculenta), as a function of conditioning prepotential. The conditioning potential duration varied from 1 to 50 ms and the amplitude between -60 and +130 mV (relative to rest). The conductance kinetics were determined at a single test potential of +20 mV (depolarization) by means of the slope of log [ninfinity - nt] vs. time relationship which defines the time constant of the process (tau). The values of tau, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 15 publications
9
36
0
Order By: Relevance
“…No such value of x could be found, which means that 1 K kinetics in this case cannot be presented by n x formalism at all. The same conclusion has also been drawn by Palti et al (1976) for analogous IK--t curves with R. esculenta.…”
Section: Typei Fiberssupporting
confidence: 81%
“…No such value of x could be found, which means that 1 K kinetics in this case cannot be presented by n x formalism at all. The same conclusion has also been drawn by Palti et al (1976) for analogous IK--t curves with R. esculenta.…”
Section: Typei Fiberssupporting
confidence: 81%
“…My results confirm the conclusions of Palti et al (1976). Potassium conductance kinetics show a clear dependency on prepulse conditions.…”
Section: Discussionsupporting
confidence: 89%
“…However, in potassium activation I c, is visible from the beginning of the experiments, immediately after the dissection and mounting of the nerve fiber. It can also be seen in the potassium currents, measured by Palti et al (1976) and Begenisich (1979). Capacitive transients, apparently including Ic,, are often subtracted from the membrane currents with an analog circuit that generates the sum of two or three exponentially decaying transients, proportional to the applied voltage step (Atwell et al, 1980;Conti, Neumcke, Nonner & St~impfli, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with those of Palti et al (12), who demonstrated that potassium current kinetics are a function of both conditioning pulse amplitude and duration (figures 5 and 6 in ref. 12). Careful examination of the conditioning induced shifts in the crayfish axon (10) reveals that there, too, the shifts are accompanied by a change in the current kinetics.…”
mentioning
confidence: 99%